Fast complete locally convex linear topological spaces - Carlos Bosch; Jan Kucera; Kelly McKennon (International Journal of Mathematics and Mathematical Sciences)
This is a study of relationship between the concepts of Mackey, ultrabornological, bornological, barrelled, and infrabarrelled spaces and the concept of fast completeness. An example of a fast complete but not sequentially complete space is presented.